Some Relations on the Double L-22-Integral Transform and Their Applications - DERNEK, AYŞE NEŞE (SPRINGER BASEL AG, 2018)
In this paper, the authors introduce the double Laplace-type integral transform L-22 and its properties. Several simple theorems dealing with general properties of the L-22-integral transform are proved. The convolution, its properties and convolution theorem are given. The main focus of this paper is to develop a method for the L-22-integral transform to solve problems in applied mathematics which involve partial differential and integral equations.
Keywords: Laplace transform; Double Laplace transform; Convolution; Integral equations; Partial differential equations; IDENTITIES